An unusual cause of intraoperative high airway pressure and ventilator failure: message to be learned - Shrestha, Anil; Parajuli, Bashu Dev; Tiwari, Pradip; Limbu, Trishant (Journal of Chitwan Medical College, 2020)
Failure of ventilation of an anesthetised patient due to problems in mechanical ventilator is not uncommon. The proper functioning of machine should be ensured before anesthetising a patient by the automated checking system or manually by the attending anaesthesiologist. However, sudden malfunction of some system of the machine during operation may cause the ventilator to stop risking the patient’s life. About one third of the equipment problems are due to anesthesia machine and one quarter of the problems are due to human error. We present a case of malfunction of anesthesia ventilator due to an unusual cause of blockage of anesthesia gas scavenging system.